ANALISIS DAMPAK KINERJA KELOMPOKTANI TERHADAP PENDAPATAN USAHATANI PADI DI KABUPATEN MANOKWARI SELATAN PROVINSI PAPUA BARAT - Entis Sutisna; Hiasinta F.J. Motulo (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACT Impac Analysis of Farmer Groups Performance towards Farmers' Income of Rice Farming System in South Manokwari District, West Papua Province. The existence of farmers' groups has a strategic role to improve the productivity and income of farmers in West Papua; therefore, it is required to enhance their performances through several approaches including monitoring. This study aims to analyze the performance of farmer groups and to assess the income of rice farmers. The research was conducted in Oransbari District, South Manokwari Regency, West Papua Province, around June 2014. Data collection was done through interviews with a semi-structured questionnaire involving 40 farmers, which were selected using simple random sampling method. Data collected was analyzed with a quantitative descriptive analysis and a non-parametric statistical analysis. The study illustrated that the performance of farmers’ respondents are in the category of good. They are also close to the ideal organizational nature and supportive of local government. The result also showed that farmer organizations have a strong legality. Farmer cooperators provide a greater absolute income than non-cooperators where the difference is very significant according to statistical tests. However, the relationship between organizational performance farmers group and revenue is still weak. The reason could occur due to weakness of the implementation of technical and institutional innovations as well as the lack of monitoring system. It is suggested that the assistance program can be improved both in term of intensity and quality including the synergy of technical innovation and institutional. Keywords: farmer groups, organizational performance, rice farming, income ABSTRAK Keberadaan kelompok tani (poktan) memiliki peran strategis dalam upaya peningkatan produktivitas dan pendapatan petani di Papua Barat. Oleh karena itu perlu ditingkatkan kinerjanya melalui berbagai cara termasuk pendampingan. Pengkajian ini bertujuan untuk menganalisis kinerja kelompok tani dan menganalisis pendapatan usahatani padi petani yang dilakukan di Distrik Oransbari, Kabupaten Manokwari Selatan, Provinsi Papua Barat, pada Juni 2014. Pengumpulan data dilakukan melalui wawancara dengan bantuan kuesioner semi terstruktur terhadap 40 orang petani yang terpilih secara acak sederhana. Data yang terkumpul di analisis secara deskriptif kuantitatif dan dipertajam dengan analisis statistik non parametrik. Hasil pengkajian menunjukkan bahwa kinerja poktan binaan termasuk dalam kategori baik, memiliki karakteristik yang mendekati sifat organisasi ideal, mendapat dukungan dari pemerintah setempat, serta memiliki legalitas yang kuat. Secara statistik usahatani padi petani kooperator berbeda nyata dengan usahatani petani padi non kooperator. Pendapatan absolut usahatani petani kooperator lebih tinggi dari non kooperator, sehingga layak untuk dikembangkan. Namun demikian, hubungan antara kinerja organisasi kelompoktani dengan pendapatan masih lemah, kontribusinya relatif rendah. Hal ini dapat disebabkan karena kurang sinergisnya sistem pendampingan pada saat implementasi inovasi teknis dan kelembagaan. Untuk itu disarankan agar program pendampingan perlu terus ditingkatkan, baik intensitas maupun kualitasnya, termasuk sinergitas implementasi inovasi teknis dan kelembagaan.Kata kunci: kelompok tani, kinerja organisasi, usahatani padi, pendapatan